Magnetic equivalent circuit model of surface type fractional-slot permanent magnet synchronous generator - Oner, Y.; Senol, I.; Bekiroglu, N.; Aycicek, E. (Extrica, 2013)
Design of permanent magnet synchronous machines becomes more of an issue for all systems lately. There are many parameters that have influence for machine design. Each parameter should have optimized and their effects on the system should be determined. Any desired pre-design have been done for machine design except a few paper and it only showed by of Finite element analysis (PEA). In this article, analytical method is used in permanent magnet synchronous machine design and the effects of geometric on the performance of machine are presented. Magnetic equivalent circuit (MEC) model is used as numeric method. It is observed that the proposed MEC model is pertinent to Speed PC-BDC model and FEA. Besides proposed MEC model provides to calculate performances of the machines which have the desirable slot/pole combinations correctly. Proposed model is applied on the recently increased fractional slot direct drive synchronous generators.
Keywords: index terms - machine design; vibration; PMSM; PEA; MEC; Engineering